12. PRIMARY MEDIASTINAL SYNOVIAL SARCOMA. (February 2015) - Ferdous, R.; Samra, S.
Abstract : Synovial sarcoma predominantly occurs in the soft tissues of the extremities. Primary synovial sarcoma in the mediastinum is exceedingly rare and only a few cases have been reported, most of which were in the posterior mediastinum. This is a case of a 68 year old lady with a previous history of left sided mediastinal tumour (MPNST) who presented with increasing shortness of breath. CT scan revealed a posterior mediastinal mass. Microscopically, the tumour was composed of hypercellular spindle cells arranged predominantly in sheets, short fascicles with focal herring bone and hemangiopericytomatous pattern. The cells were oval to spindle with overlapping nuclei, inconspicuous nucleoli with scant indistinct cytoplasm. The stroma shows patchy areas of thick intercellular collagen and plentiful scattered thick and thin walled staghorn vessels. No definite epithelial elements were seen. The tumour cells showed strong diffuse staining for vimentin and CD99. Weak, patchy positivity for EMA and BCL-2 were noted. This is further confirmed by FISH which showed rearrangement of SS18 (18q11.2) in a significant proportion of tumour nuclei.